UMP, Etiqa help 200 asnaf children receive school necessities - UMP, PNC (2019)
A total of 200 primary school students from 11 schools around Pekan involving children from low-income families (B40) were delighted to receive new clothes and school necessities during the Back to School 2019 programme organised by Universiti Malaysia Pahang (UMP) in cooperation with Etiqa Family Takaful Berhad and UMP Foundation in Pekan on 19 November 2019.